"A Death Like his": Saul's Privation and Restoration of Sight as Prophetic Formation in Acts 9. (2nd January 2018) - Booth, Adam David Patrick
ABSTRACT: At the start of Acts 9, Saul is a vigorous promoter of violence against followers of "the Way." By the end of the chapter, he is a powerful prophet proclaiming Jesus as Lord. The transformation is presented in part through Saul's embodied experience of the privation and subsequent restoration of his sight. The author understands this narrative as invoking a common trope of a divine figure temporarily rendering a potential assailant sightless as a means of protection. Saul's privation experience is then presented as a parallel to Jesus' death. In the topsy-turvy post-Easter world, such an experience leads to "resurrection, " which in Saul's case is no mere restoration of physical sight, but rather a remaking of his body and character which makes him both physically weaker and powerfully prophetic. This narrative forces us to attend to the complex realignment of notions of power in Luke-Acts, and has pastoral ramifications for Christians today, including, but not limited to, the full integration of person with disabilities into ministerial structures.